Extraskeletal myxoid chondrosarcoma of the buttock: a case report and literature review - Ji, Xinghua; Wei, Jinzheng; Li, Xiaoqiong; Zhang, Wei; Xing, Zejun (Frontiers in Oncology, 2023)
Background: Extraosseous myxoid chondrosarcoma (EMC) is extremely rare, and the case we report is of a particular site with partial bone destruction.Case presentation: This case report can further strengthen the understanding of EMC and guide clinical treatment. The patient presented with a right buttock mass that was present for 1 year and that had gradually enlarged with tenderness for 6 months. The diagnosis was EMC. The interventions included puncture biopsy, surgical resection, and postoperative chemotherapy. The tumor was resected extensively, and the postoperative recovery was satisfactory. There was no recurrence or metastasis during the follow-up for 18-month.The case we reported occurred in the pelvic cavity, which has not been 2 previously reported in the literature, and there was partial bone destruction. Complete resection of the tumor was performed, and a satisfactory prognosis was achieved.